Clinical hypnosis in palliative care - Simone II, Charles B. (Annals of Palliative Medicine, 2018)
The January 2018 issue of Annals of Palliative Medicine is a focused issue entitled, “Clinical Hypnosis in Palliative Care: Neural Correlates, Clinical, Psychological and Spiritual Therapies” that is guest edited by Dr. Maria Paola Brugnoli. Dr. Brugnoli is on the Interdisciplinary Research Team in Neurobioethics and the UNESCO Chair at Pontifical Athenaeum Regina Apostolorum in Roma, Italy.